Особливості стану слизової оболонки порожнини рота і тканин пародонта в дітей-інвалідів із порушеннями психіки - Гавриленко, М. А.; Gavrilenko, M. A. (УМСА, 2015)
Було обстежено 98 дітей-інвалідів із психічними розладами у віці від 2 до 18 років, які проживають у м. Запоріжжі та Запорізькій області. Виявлено високу поширеність та інтенсивність захворювань тканин пародонта. Было обследовано 98 детей-инвалидов с психическими расстройствами в возрасте от 2 до 18 лет, проживающих в г. Запорожье и Запорожской области. Выявлены высокая распространенность и интенсивность заболеваний тканей пародонта. 98 disabled children with mental disorders in children aged 2 to 18 years living in Zaporizhzhya and Zaporizhzhya region were observed. High prevalence and intensity of diseases of parodontium tissues. Analyzing the data of contemporary literature it can be concluded that the provision of dental care to children with mental disorders requires special attention. In practice, we face to the problem of impossibility to perform the existing protocols of dental treatment as well as implementation of preventive procedures for such children. It is connected with the specific behavior of children with mental disorders. In this group of such patients it is necessary to optimize the development of modern methods of prevention and to improve the dental care approach.
Features of condition of periodontal tissues in disabled children with mental disorders
Keywords: діти-інваліди з порушеннями психіки; гінгівіт; пародонтит; дети-инвалиды с нарушениями психики; гингивит; disabled children with mental disorders; gingivitis; periodontitis